Knowledge worker fitness in the workspace: self-managing at the edge of chaos. Issue 2 (3rd April 2021) - Guthrie, Cameron
ABSTRACT: Today's knowledge work environment is one of frequent interruptions, unnecessary distractions, essential interactions and valuable fragments of solitary work. There is an urgent need to better understand how knowledge workers juggle their competing, intertwining activities to get work done. Drawing on complexity theory we conceptualise the workplace as a complex adaptive system where knowledge workers evolve across a mountainous "fitness landscape", made up of peaks and valleys that represent various levels of "fitness" for productive work. Using a case study design and detailed observation of knowledge workers, we find that they often rely on stable, but sometimes sub-optimal workgroup routines and the search costs of exploring the landscape prevent them from finding and climbing more productive distant peaks. The fitness landscape metaphor is useful for understanding knowledge worker self-management behaviours and provides a new frame to study knowledge worker productivity.